Relationship between Family Support and Aggregate Activity of Adults in Visit to Integrated Coaching Post (Posbindu) - Iftah Sofia Syfa; Wachidah Yuniartika (Jurnal Berita Ilmu Keperawatan, 2022)
The level of activeness of integrated coaching post (posbindu) visits in Muncar Village, Susukan District is still relatively low, with a value of 50,4% of the 127 integrated coaching post (posbindu) participants who were not active in visiting integrated coaching post (posbindu). The inactivity of participants in participating in integrated coaching post (posbindu) activities is caused by several factors, one of which is a reinforcing factor, namely the lack of family support. The purpose of this study was to determine family support with adult aggregate activity in visits to integrated coaching post (posbindu) in Muncar Village, Susukan District. This research method quantitative research with cross sectional. The population of 127 integrated coaching post (posbindu) participants using simple random sampling technique and Inclusion criteria: the aggregate of adults aged 17-55 years, registered in integrated coaching post (posbindu) activities live with family members obtained 67 respondents. The research instrument used a questionnaire containing 18 questions about family support and the attendance list for posbindu participants from February 2019 - to January 2020. The analysis bivariate technique used test analysis data used Chi Square because the data contribute normally. The results of the study the majority of family support is lacking as many as 33 people or 49.3%. The activity level of the majority of respondents is inactive as many as 37 people or 55.2%. The results of the correlation test between family support and active visits in the adult aggregate are p-value 0.001. The conclusion is that there is a relationship between family support and adult aggregate activity in visits to integrated coaching post (posbindu) in Muncar Village, Susukan District. The recommendation for integrated coaching post (posbindu) in Muncar Village is to increase knowledge about the importance of family support so that participants can actively attend every month so that their health can be controlled regularly every month